2008
DOI: 10.1302/0301-620x.90b9.20688
|View full text |Cite
|
Sign up to set email alerts
|

The effect of closed- and open-wedge high tibial osteotomy on tibial slope

Abstract: Radiographs of 110 patients who had undergone 120 high tibial osteotomies (60 closed-wedge, 60 open-wedge) were assessed for posterior tibial slope before and after operation, and before removal of the hardware. In the closed-wedge group the mean slope was 5.7 degrees (SD 3.8) before and 2.4 degrees (SD 3.9) immediately after operation, and 2.4 degrees (SD 3.4) before removal of the hardware. In the open-wedge group, these values were 5.0 degrees (SD 3.7), 7.7 degrees (SD 4.3) and 8.1 degrees (SD 3.9) respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 13 publications
8
116
1
1
Order By: Relevance
“…Inappropriate alteration of the sagittal inclination can compromise the normal knee kinematics (El-Azab et al, 2008). Previous data showed that increasing the posterior slope aids in decreasing stress on the posterior cruciate ligament (Lobenhoffer et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate alteration of the sagittal inclination can compromise the normal knee kinematics (El-Azab et al, 2008). Previous data showed that increasing the posterior slope aids in decreasing stress on the posterior cruciate ligament (Lobenhoffer et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Achieving overcorrection with a high tibial osteotomy (HTO) is important for achieving long-term success in the treatment of unicompartmental arthrosis [6,42]. Although the closing wedge osteotomy can be used to correct malalignment, the technique has several limitations [1,3,6,9]. These include the inability to adjust alignment without additional surgery and shortening results from removal of bone segments.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the medial opening wedge osteotomy has gained popularity as another option to avoid the complications associated with the closing wedge technique. This technique also requires acute correction and no ability to correct any residual deformity [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…No obstante, las alteraciones que producen las osteotomías en la pendiente tibial obligan a conocer el estado de los ligamentos cruzados para decidirnos por una u otra técnica. La osteotomía de sustracción disminuye la caída del platillo tibial, mientras que la de adición la aumenta 73 . Hemos encontrado consenso en lo referente a la indicación de la prótesis unicompartimental: mayores de 50 años con artrosis limitada en el compartimento medial y que no deben indicarse exclusivamente al paciente joven.…”
Section: Tratamiento Quirúrgicounclassified